The Effects of Fiscal Policy and Monetary Policy on Borrowing Costs and Credit Access for SMEs: An Empirical Study - Zakaria, Syawal (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The objective of this study is to investigate the impact of fiscal policies (FP) on borrowing costs and credit access (BCAC) for SMEs, considering the role of monetary policy (MP) as a the second independent factor. This research aims to understand more deeply how fiscal and monetary policies can be utilized to support growth and access to finance for SMEs, as well as identify remaining barriers to access to finance. Through comprehensive analysis, this study is expected to provide effective policy recommendations to improve access to credit for SMEs, which in turn can support economic growth and job creation. This study adopts a quantitative research design using statistical analysis to examine the impact of fiscal policies on borrowing costs and credit access for Small and Medium Enterprises (SMEs). The analysis will be conducted using the SMARTPLS 3.0. Sample size based on valuable samples are 120 of SME. The sampling technique used in this study will be purposive sampling. This approach will involve selecting SMEs that meet specific criteria, such as size, sector, and eligibility for relevant government programs or incentives. Result of this study state Fiscal Policy (FP) and Monetary Policy (MP) have a significant effect on Borrowing Costs and Access to Credit (BCAC).